Case report: Medulla oblongata and cervical cord reperfusion injury after intracranial vertebral artery angioplasty and stenting - Wang, Guiping; Zuo, Bo; Jia, Jia; Huang, Jinlong; Xi, Gangming; Yang, Zhigang (Frontiers in Neurology, 2023)
Background White cord syndrome is an uncommon complication characterized by delayed neurologic deterioration with no other identified cause after spinal decompression surgery. Its etiology is attributed to spinal cord reperfusion injury. Here, we present the first case of an extended version of white cord syndrome, with concomitant involvement of the medulla oblongata and cervical cord reperfusion injury after intracranial vertebral artery angioplasty and stenting. Case presentation A 56-year-old male suffered an ischemic stroke in the right anteromedial medulla oblongata. Angiography revealed bilateral vertebral artery stenosis in the intracranial segment. We performed elective left vertebral artery angioplasty and stenting. An intraoperative flow arrest in the left VA occurred and was stopped after the withdrawal of the catheter. Several hours after the operation, the patient developed occipital headache, back neck pain, dysarthria, and worsening left-sided hemiplegia. Magnetic resonance imaging revealed hyperintensity and swelling in the medulla oblongata and cervical cord, in addition to small medullary infarction. A digital subtraction angiography revealed intact vertebrobasilar arteries and patency of the left vertebral artery, left posterior inferior cerebellar artery, and implanted stent. We considered that the reperfusion injury had caused the complication. After treatment, the patient’s symptoms and neurologic deficits greatly improved. He achieved a favorable outcome at the 1-year follow-up, with normal intensity restored in the medulla oblongata and cervical cord on magnetic resonance imaging. Conclusion Concomitant reperfusion injury in the medulla oblongata and cervical cord secondary to vertebral artery angioplasty and stenting is extremely rare. However, this potentially devastating complication requires early recognition and prompt treatment. Maintaining the antegrade flow during vertebral artery endovascular treatment is a precaution against reperfusion injury.